2020
DOI: 10.1590/1518-8345.3239.3256
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the work environment and intention of perioperative nurses to quit work

Abstract: Objective: to investigate how the perioperative work environment affects work dissatisfaction, professional exhaustion and the perception of the quality of care about the intention of abandoning the work of perioperative nurses. Method: cross-sectional study with 130 nurses working in the surgical area of a high-tech Spanish public university hospital. The scale of the nursing practice environment, Maslach’s exhaustion inventory, the questions about job satisfaction, the perception of the care quality and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
16

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 35 publications
0
17
0
16
Order By: Relevance
“…Despite the difficulties of the health crisis, the work engagement levels of the sample nurses were high during the first wave of the pandemic. Nurses working in medical and critical hospital units obtained lower mean scores—46.6% for Spanish nurses—so the Spanish health system should design and implement strategies to increase these scores, to improve the job satisfaction and work engagement and to prevent the intention to leave, in these settings [ 41 ]. Moreover, the group of men obtained the lowest mean scores in vigor dimension, but they only 22.6% of the sample.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the difficulties of the health crisis, the work engagement levels of the sample nurses were high during the first wave of the pandemic. Nurses working in medical and critical hospital units obtained lower mean scores—46.6% for Spanish nurses—so the Spanish health system should design and implement strategies to increase these scores, to improve the job satisfaction and work engagement and to prevent the intention to leave, in these settings [ 41 ]. Moreover, the group of men obtained the lowest mean scores in vigor dimension, but they only 22.6% of the sample.…”
Section: Discussionmentioning
confidence: 99%
“…The literature supports those findings [32,33]. Additionally, the perioperative nurses identified that increased stress and adverse situations with surgeons had caused some nurses to leave the hospital [34]. The surgeon traditionally has the perioperative team leader role, and they perceive the workplace more positively than others.…”
Section: Discussionmentioning
confidence: 55%
“…Intention to leave the job has been a benchmark used by other researchers to assess the ability of institutions to retain nursing staff (Sillero‐Sillero & Zabalegui, 2020). The decrease in nursing turnover, assessed by the intention of nursing staff to leave their jobs, was related to leadership training and improved relations between physicians and nurses.…”
Section: Discussionmentioning
confidence: 99%